Enhancing Bank Supervision in Asia: Lessons Learned from the Financial Crisis - Michael J. Zamorski; Minsoo Lee (Asian Development Bank (ADB), 2015)
The global financial crisis underlined that sound and effective bank regulation is vital to financial stability. Assessments of the global financial crisis invariably point to ineffective finance regulation and supervision as the main reasons for the onset of the crisis and its severity. In particular, lapses in banking regulation contributed significantly to the outbreak. The crisis reflected the failure of regulatory authorities to keep pace with financial innovation. Bank supervision had been weak by any measure. Supervisors did not conduct regular onsite bank inspections or examinations of sufficient depth. They did not properly implement risk-based supervision, and they failed to identify shortcomings in banks' risk-management methods, governance structures, and risk cultures. Meanwhile, offsite surveillance systems rely too heavily on banks' self-reported data to effectively monitor risk. Banking regulation is the primary safeguard against financial instability, but it should be supplemented by macroprudential policies and other new policy instruments now available to regulatory authorities.
hdl:11540/5103
Keywords: G01; G18; G21; G28; 330; Basel Committee's core principles; finance regulation and supervision; global financial crisis; macroprudential policy